UJI ORGANOLEPTIK NUGGET DAGING SAPI DENGAN PENAMBAHAN TEPUNG DAUN KELOR - M. Aan Lutfi Hadiansyah; Nita opi ari kustanti; Resti Yuliana Rahmawati (AVES: Jurnal Ilmu Peternakan, 2020)
The main reason of this study was to determine the organoleptic test of beef nuggets with the addition of Moringa leaf flour. The questionnaire was taken at the Balitar Islamic University. Selection of respondents, namely selecting students who are currently studying to be respondents. The method of analysis uses the ANOVA method and the scoring system uses the hedodonic test method, where "1" is the lowest point and "5" is the highest point that can be obtained by each variable, and uses index calculations or assessment intervals. from the hedodonic method to put the final category at the end of the analysis. From the results of the analysis using the ANOVA method and the DMRT further test, the following results were obtained, with the ANOVA method all parameters showed the results of ƒcount> table 5%, while with the DMRT method all parameters showed that the results of P1 and P2 were not significantly different, except the aroma showed results P0, P1 and P2 is not significantly different. The conclusion of this organoleptic test is the color parameter 3.1333333 (greenish white), aroma 3.1666667 (typical nuggets), taste 3.5666667 (delicious), texture 3.6333333 (chewy) and preference 3.6333333 (like), seen from the five parameters that indicate nuggets are well received by examiners, then for the best treatment is P1 (addition of 2% Moringa leaves)